FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RENTANG WAKTU KETEPATAN PENYAMPAIAN LAPORAN KEUANGAN KE PUBLIK STUDI DI BURSA EFEK INDONESIA 2005-2009 - Wahyuni Yusria Ningsih (AkMen JURNAL ILMIAH, 2016)
Financial statement information has the optimal benefit if available in time for its needs . The determination of the time of publication of financial statements is important , therefore, the regulator has issued a deadline for it . Span of submission of financial statements to be important in determining the benefits of financial reporting information itself . The purpose of this study was to determine the factors that influence the accuracy of the span of submission of financial statements to the public . The data used is a manufacturing company with the period 2005 to 2009 the number of observations of 244 samples. This study examines whether profitability , leverage , firm size , the audit opinion , the auditor turnover , and the span of the completion of the audit of annual financial statements affect the span accuracy submission of financial statements to the public . Analysis tools used in testing these hypotheses is multiple regression .